2010
DOI: 10.1186/1471-2334-10-201
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders in TB/HIV co-infected patients in Ethiopia

Abstract: Background-The relationship between TB/HIV co-infection and common mental disorders (CMD) has been scarcely investigated. In this study, we compared the occurrence of CMD in TB/HIV co-infected and non-co-infected HIV patients in Ethiopia.Methods-We conducted a cross sectional study in three hospitals in Ethiopia from February to April, 2009. The study population consisted of 155 TB/HIV co-infected and 465 non-co-infected HIV patients. CMD was assessed through face to face interviews by trained clinical nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
110
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(135 citation statements)
references
References 37 publications
(50 reference statements)
16
110
6
Order By: Relevance
“…11 In other studies, it was reported that HIV patients had a lower QoL as compared to the general population 14 and that TB patients had a lower QoL as compared to their neighbors.…”
mentioning
confidence: 99%
“…11 In other studies, it was reported that HIV patients had a lower QoL as compared to the general population 14 and that TB patients had a lower QoL as compared to their neighbors.…”
mentioning
confidence: 99%
“…Tuberculosis and HIV are two chronic infective medical diseases which have been found to be associated with psychiatric comorbidity [38,39] and this furthers affect the quality of life of the sufferers [40][41][42][43][44][45][46][47][48][49][50][51][52]. The greatest risk factor to the TB infection is known to be Human Immunodeficiency Virus (HIV) [27][28][29]46]. This is because the virus compromises the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…A mere diagnosis of these chronic medical diseases can pose serious psychological trauma for the sufferer, giving rise to varied psychiatric symptoms and comorbidities [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The situation has greatly worsened with the recent surge in co-infection of tuberculosis with HIV infection [27][28][29]. However, the introduction of chemotherapy has significantly reduced the morbidity and mortality [30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations